(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
This report presents an unusual case of firearm-related death in a 40-year-old male. Autopsy examination revealed bloodstained clothing and a split laceration measuring 15 × 2.5 cm x bone deep over the chin, consistent with a firearm entry wound. The wound had irregular margins, cherry-red discoloration of underlying tissues, and a comminuted mandibular fracture. Multiple teeth were broken, and fractures were noted in the nasal bone. The oral cavity also showed cherry-red discoloration. Blackening of the skin, non-removable on wiping and without singeing of surrounding hair, was noted along the upper edge of the lacerated wound. A semicircular muzzle imprint was present 1.9 cm to the right, with its lower margin adjoining the wound. The entry wound was located 152 cm above the heel. Scalp examination revealed ecchymosis, with multiple fractures of varying dimensions on the outer and inner tables of the skull. The dura was torn in several places. Numerous pellets were found dispersed in the cranial cavity, after striking the base of the skull, along with a plastic wad in the left parietal region of the brain. Both subarachnoid and subdural hemorrhages were present all over the brain at places. Internal organs appeared pale on cut section. Based on the autopsy findings and circumstantial evidence, the cause of death was determined to be craniocerebral trauma due to a firearm injury. The pattern and characteristics of the injuries were consistent with a contact-range shot and supported the conclusion of a suicidal manner of death.